2020
DOI: 10.3853/j.2201-4349.72.2020.1763
|View full text |Cite
|
Sign up to set email alerts
|

Two new deep-water species of Ampharetidae (Annelida: Polychaeta) from the eastern Australian continental margin

Abstract: Two new species, Melinnopsis gardelli sp. nov. and Melinnopsis chadwicki sp. nov. (Annelida, Ampharetidae, Melinninae), are described from deep waters off the east coast of Australia. One hundred and 11 specimens were collected during RV Investigator voyage IN2017_V03 in May-June 2017 using a beam trawl at lower bathyal depths (1000-2500 m). This is the first record of Melinnopsis from the eastern Australian coast. The two new species are morphologically similar, but differ by methyl blue staining pattern, sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Phylogenetic topologies reveal sister group relationships between both species of Ramisyllis, with a clear divergence in COI and 16S (which show faster mutations rates than the nuclear 18S and 28S). The very high COI distances between both species of Ramisyllis agree with previous studies delimitating species in syllids and annelids in general (Aguado et al, 2019;Álvarez-Campos et al, 2017;Kvist, 2016;Lobo et al, 2016;Nygren et al, 2018), as well as those found for the 16S (Bastrop et al, 1998;Gunton et al, 2020;Miglietta et al, 2010;Radashevsky et al, 2016) and ITS2 markers (Vivien et al, 2015). Conversely, the 28S distance was 1 order of magnitude lower but still significant since this is a slow evolving gene and the obtained distances were similar to those among other syllids (Aguado et al, 2019).…”
Section: Ramisyllis Kingghidorahi a New Branching Speciessupporting
confidence: 89%
“…Phylogenetic topologies reveal sister group relationships between both species of Ramisyllis, with a clear divergence in COI and 16S (which show faster mutations rates than the nuclear 18S and 28S). The very high COI distances between both species of Ramisyllis agree with previous studies delimitating species in syllids and annelids in general (Aguado et al, 2019;Álvarez-Campos et al, 2017;Kvist, 2016;Lobo et al, 2016;Nygren et al, 2018), as well as those found for the 16S (Bastrop et al, 1998;Gunton et al, 2020;Miglietta et al, 2010;Radashevsky et al, 2016) and ITS2 markers (Vivien et al, 2015). Conversely, the 28S distance was 1 order of magnitude lower but still significant since this is a slow evolving gene and the obtained distances were similar to those among other syllids (Aguado et al, 2019).…”
Section: Ramisyllis Kingghidorahi a New Branching Speciessupporting
confidence: 89%